INVERSE RELATIONSHIP BETWEEN THE ANTIOXIDANT ACTIVITY OF STRUCTURALLY RELATED SYNTHETIC MONOPHENOLS AND THEIR TOXICITY IN TUMOR CELLS - P. I. Gaynutdinov; P. M. Kozhin; A. V. Chechushkov; G. G. Martinovich; S. V. Kholshin; N. V. Kandalintseva; N. K. Zenkov; E. B. Menshchikova (Сибирский научный медицинский журнал)
The aim of the study was to study investigate the relationship between the antioxidant activity of new synthetic structurally related water-soluble monophenols and their effect on the tumor cell viability in vitro. Material and methods. Five original hydrophilic sulfur- and selenium-containing monophenols with varying length of the hydrocarbon chain of the para -alkylthiosulfonate substituent, the amount of tert -butyl ortho -substituents and the «S-S» fragment structure are synthesized: sodium 3-(3'- tert -butyl-4'-hydroxyphenyl)ethyl thiosulfonate (TS-12), sodium 3-(3'- tert -butyl-4'-hydroxyphenyl)propyl sulfonate (S-13), sodium 3-(3'- tert -butyl-4'-hydroxyphenyl)propyl seleniumsulfonate (SeS-13), sodium 3-(3'- tert -butyl-4'-hydroxyphenyl)propyl thiosulfonate (TS-13), sodium 3-(3',5'-di- tert -butyl-4’-hydroxyphenyl)propyl thiosulfonate (TS-17). The antioxidant activity of the compounds was determined in a cell-free model test system by the ability to inhibit the luminol-dependent chemiluminescence of free radical-generating azo compound AAPH. Antitumor cytotoxicity was evaluated by their effect on the viability of human histiocytic lymphoma cell line U937 (monocyte/macrophage-like cells) and human breast adenocarcinoma cell line MCF-7 in the MTT test. Results and discussion. All tested phenolic compounds exerted antioxidant activity in the cell-free model system (inhibition of azo initiator radical AAPH•) and cytotoxicity against U937 and MCF-7 cells, the effect depended on the dose and structure of the molecule. There was a direct relationship between the structure of monophenols and their ability to inhibit the viability of tumor cells of different lines, regardless of the origin of the latter, myeloid (U937) or epithelial (MCF-7), and growth type (respectively anchorage-independent and attached), as well as the concentration range of compounds (respectively from 100 to 500 μM and from 2 to 150 μM). At the same time, the relationship between the antioxidant activity of monophenols and their cytotoxicity was inverse (when SeS-13 was excluded from analysis), which may be related both to the ability of the tumor to self-defense against reactivate oxygen metabolites and to the indirect pro-oxidant effect of phenolic compounds.